Prudential regulation in an artificial banking system - Pedro Dias Quinaz; José Dias Curto (Economics: The Open-Access, Open-Assessment E-Journal, 2016)
This study is an exploratory analysis of the economic role of banks under different prudential frameworks. It considers an agent-based computational model populated by consumers, firms, banks, and a central bank whose out-of-equilibrium interactions replicate the conjunct dynamics of a banking system, a financial market and the real economy. A calibrated version of the model is shown to provide an intelligible account of several recurring economic phenomena, thus constituting a favorable ground for policy analysis. The investigation provides a valuable methodological contribution to the field of banking research and sheds new light on the role of banks and their prudential regulation. Specifically, the results suggest that banks are key economic agents. Through their financial intermediation activity, credit institutions facilitate investment and promote growth.
Keywords: C63; G28; 330; agent-based computational model; financial intermediation; prudential policy; bank regulation